2010
DOI: 10.3390/molecules15053507
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of (+)-Pinoresinol Isolated from Sambucus williamsii

Abstract: Abstract:In this study, we investigated the antifungal activity and mechanism of action of (+)-pinoresinol, a biphenolic compound isolated from the herb Sambucus williamsii, used in traditional medicine. (+ )-Pinoresinol displays potent antifungal properties without hemolytic effects on human erythrocytes. To understand the antifungal mechanism of (+)-pinoresinol, we conducted fluorescence experiments on the human pathogen Candida albicans. Fluorescence analysis using 1,6-diphenyl-1,3,5-hexatriene (DPH) indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…Hwang et al . () showed that pinoresinol inhibits the growth of Candida albicans by causing damage to the fungal plasma membrane. Other limited studies revealed the growth inhibitory effect of lignans against different fungi, including mycotoxin producers such as Aspergillus flavus , A. niger and F. verticillioides (Céspedes et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al . () showed that pinoresinol inhibits the growth of Candida albicans by causing damage to the fungal plasma membrane. Other limited studies revealed the growth inhibitory effect of lignans against different fungi, including mycotoxin producers such as Aspergillus flavus , A. niger and F. verticillioides (Céspedes et al .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 2 attenuates inflammatory responses of microglia and could be useful in modulation of inflammatory status in brain disorders (Jung et al, 2010). Lignan 2 was shown to possess fungicidal activities and therapeutic potential as an antifungal agent for the treatment of fungal infectious diseases in humans (Hwang et al, 2010). It exhibited inhibitory activity against rat intestinal maltase with an IC 50 value of 34.3 μM (Wikul et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of certain types of breast cancer in premenopausal women is lowered by pinoresinol ingestion (Brown 2012). Pinoresinol presents activity against both human pathogenic fungi (Hwang et al 2010) and Gram-positive bacteria (Céspedes et al 2006). Secoisolariciresinol exhibited a significant antifungal activity on fungi of white rooting and wood staining (Céspedes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%